Implementasi Dan Inovasi Pembiayaan Syariah Cash Waqf Linked Sukuk (CWLS) - Daryn Salsabila (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The development of Islamic finance has exhibited notable progress. Cash Waqf Linked Sukuk, also known as CWLS, is a type of innovation in the field of Islamic finance. This instrument is a form of state commitment in supporting the National Movement for Cash Waqf (GNWU) to increase a sense of care and social solidarity and realize efforts to alleviate poverty, social inequality, and realize equitable development in Indonesia. Integrating three distinct sectors, namely the Islamic Social Finance sector, the commercial financial sector, and state or fiscal finance, CWLS is an innovative and intelligent breakthrough. Through waqf, wakif or cash waqf will be facilitated to invest either temporarily or permanently so that they can place their money in investment instrument that are safe, productive, blessed, and beneficial by sharia principles.